2022
DOI: 10.3390/molecules27144585
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Activity of Carboxymethyl Cellulase Enzyme Using Highly Stable Selenium Nanoparticles Biosynthesized by Bacillus paralicheniformis Y4

Abstract: The inorganic selenium is absorbed and utilized inefficiently, and the range between toxicity and demand is narrow, so the application is strictly limited. Selenium nanoparticles have higher bioactivity and biosafety properties, including increased antioxidant and anticancer properties. Thus, producing and applying eco-friendly, non-toxic selenium nanoparticles in feed additives is crucial. Bacillus paralicheniformis Y4 was investigated for its potential ability to produce selenium nanoparticles and the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 82 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Compared with the inorganic Se [32], nano-Se has higher bioavailability, lower toxicity, and controlledrelease effects, which can be a source of Se supplement for Se-deficient population [33] with the potential anticancer activity [34] and antiviral and antibacterial activities as well as coloring [35]. In the present study, the formation of extracellular nano-Se is a simple process T A B L E 3 Total Se contents and Se speciation in the cells of strain YLX-1 T during the growth under 1.5 mg Se (as Na 2 SeO 3 )/L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the inorganic Se [32], nano-Se has higher bioavailability, lower toxicity, and controlledrelease effects, which can be a source of Se supplement for Se-deficient population [33] with the potential anticancer activity [34] and antiviral and antibacterial activities as well as coloring [35]. In the present study, the formation of extracellular nano-Se is a simple process T A B L E 3 Total Se contents and Se speciation in the cells of strain YLX-1 T during the growth under 1.5 mg Se (as Na 2 SeO 3 )/L.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the inorganic Se [32], nano‐Se has higher bioavailability, lower toxicity, and controlled‐release effects, which can be a source of Se supplement for Se‐deficient population [33] with the potential anticancer activity [34] and antiviral and antibacterial activities as well as coloring [35]. In the present study, the formation of extracellular nano‐Se is a simple process of selenite detoxification which can prevent cellular Se overload; meanwhile, it could be a promising strategy to synthesize nano‐Se to avoid tedious process of cell disruption and solvent extraction during nano‐Se separation [36].…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 , 14 ], Bacillus spp. [ 15 , 16 , 17 ], Stenotrophomonas maltophilia [ 18 ], and Pseudomonas alcaliphila [ 19 ], which are capable of synthesizing uniformly sized spherical SeNPs both inside and outside the cell. More importantly, in recent years, biological treatment involving microorganisms has been considered the preferred and sustainable alternative due to its low cost and ecofriendliness.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Recently, increasing evidence has shown that inorganic antioxidant enzyme nanoparticles (NPs) can treat multiple diseases and show better stability and efficacy than natural enzymes. [ 10 ] Furthermore, Fe 3 O 4 NPs—the most widely used nanoenzyme—have SOD‐ and catalase (CAT)‐like activities that convert superoxide to H 2 O 2 and eventually to O 2 . [ 11 ] Additionally, local Fe 3 O 4 NPs administration might relieve inflammatory pain in mice by attenuating inflammatory cell infiltration and pro‐inflammatory signaling and scavenging microenvironment free radicals.…”
Section: Introductionmentioning
confidence: 99%